Small Ruminant Systems in Palestine and the Role of Local Agricultural and Industrial by- Products in these Systems - Jamal Amin Mohammad Hammad (My University, 2003)
Small ruminants are considered a very important element in the A Palestinian agricultural community. This research was conducted to study this important side of the Palestinian agriculture through studying the main raising systems, analyzing them and highlighting these systems. Also, the study aims to search for alternatives for feed for the major agricultural and industrial by- products available in Palestine. A questionnaire was designed to examine the sheep and goats systems. A total of 400 questionnaires were distributed in Nablus, Salfeet, Tobas and Jordan Valley including 50 villages and city camps. This questionnaire resembles more than 10% of the total registered farmers in the Ministry of Agriculture .The experience and the size of the farms were the main factors to accept or reject the questionnaire. The results of the study showed that 90% of farms of the intensive system are using hormones to control reproduction, while this percent was 50% in the other two systems. This research showed that the highest fertility rate was observed in the second system followed by the first system, then the third. The highest percentage of twins was observed in the first system, followed by the third, then the second. The raising system had a significant effect (p<0.05) on the weight of the newborn, and on the mortality percentage of the flocks in the studied systems.This study also showed that there were a significant differences (p<0.05) in milking period the highest of which was observed in the third system, the second, then the first. This was reversely correlated with the quantities of milk production according to the other two systems. The productivity of sheep in the first system was the highest compared to other systems. Also the study showed that the use of by- products was significant among the three systems. There were significant differences (p<0.05) considering the age of Hocks and using of records. The age of sheep in the third system was larger than the age in the first and second system. The majority of farmers in the third system did not have records compared to the first and second systems.

تعتبر المجترات الصغيرة عنصراً مهماً في الزراعة الفلسطينية والمجتمع الفلسطيني، وقد جاءت هذه الدراسة لإلقاء الضوء على هذا الجانب المهم من الزراعة الفلسطينية من خلال دراسة أنظمة تربيتها السائدة في فلسطين وهي: المكثف، وشبه المكثف، والرعوي، وتحليلها لمحاولة خفض تكاليف الانتاج عن طريق خفض تكاليف الأعلاف وإلقاء الضوء على هذه الأنظمة، وهدفت هذه الدراسة إلى البحث عن بدائل للأعلاف من المخلفات النباتية الصناعية الأكثر توافراً في فلسطين، مثل مخلفات الحمضيات وجفت الزيتون وأوراق الموز وتفل البندورة وغيرها، ولتحقيق الدراسة صممت الاستمارات لتناسب أنظمة الرعي الثلاث ووزعت على أكثر من خمسين قرية في محافظات نابلس، وسلفيت، وطوباس، والأغوار، بما في ذلك المدن والمخيمات وقد تم جمع أكثر من 400 استمارة تمثل أكثر من 10% من مجموع المزارعين المسجلين لدى دوائر الزراعة وقد اعتمدت الخبرة وحجم الزراعة كعوامل رئيسة لقبول أو رفض الاستمارة وقد تم اختيار 300 استمارة من أصل 400 ثم أدخلت للحاسوب وتم معالجتها بواسطة برنامج التحليل الإحصائي SPSS وتم استخراج نتائج التحليل وجدولتها والتعليق عليها، وبينت الدراسة أن هناك تبابناً بين الأنظمة الثلاثة في العديد من البيانات، إذ تبين أن 90% من المزارع ضمن نظام تربية الأغنام المكثف، مقابل 40% من المزارع في النظامين الأخرين يستخدمون الاسفنجات على الترتيب، وتبين الدراسة أن أعلى معدل للخصوبة كان في مزارع النظام الثاني، يليه النظام الاول ثم الثالث، وكانت أعلى نسبة للتوائم في النظام الاول ثم الثالث فالثاني، وقد كان لنظام التربية تأثير معنوي (0.05 > P ) على وزن المواليد ونسبة النفوق في القطعان في الأنظمة المدروسة، وبينت الدراسة أن هناك فروقات معنوية (0.05 > P )فيما يتعلق بطول فترة الحلب حيث كانت الأعلى في النظام الثالث يليها الثاني ثم الأول، حيث كان ذلك يتناسب عكسياً مع كميات الحليب المنتجة من الأغنام حسب الأنظمة المدروسة. إذ كان الانتاج في الأغنام المرباة ضمن النظام الأول هي الأعلى مقارنة بكل من النظامين الآخرين، وقد كان دور الاسرة في التربية هاما في النظام الثالث مقارنة بالنظامين الاخرين، ودلت الدراسة ايضا على ان استخدام المخلفات تميز بشكل معنوي بين الانظمة المختلفة، حيث كان 80% من المزارع يعتمدون على المخلفات في التغذية، وقد كانت هناك فروقات معنوية (0.05 >P ) فيما يتعلق بمعدل عمر القطعان واستخدام السجلات، فقد كان عمر الأغنام في النظام الثالث أكبر بكثير من عمرها في النظام الأول والثاني كما أن غالبية المزارع في النظام الثالث لا تحوي سجلات مقارنة بالنظامين الاول والثاني.
أنظمة تربية المجترات الصغيرة في فلسطين ودور المخلفات الزراعية والصناعية في هذه الأنظمة